Tembusu virus infection in laying chickens: Evidence for a distinct genetic cluster with significant antigenic variation. Issue 4 (13th December 2021) - Yu, Ziding; Ren, Hang; Sun, Mengxu; Xie, Wanying; Sun, Songsong; Liang, Ning; Wang, Haijian; Ying, Xiaoqiang; Sun, Yuxi; Wang, Yuling; Zheng, Yunping; Hu, Xueying; et al.
Abstract: Tembusu virus (TMUV) associated disease is a growing cause of egg production decrease and encephalitis in domestic waterfowl, with expanding distribution. In previous studies, TMUV isolates were phylogenetically classified into two genetic lineages and different clusters with varied pathogenicity. However, little is known about the phenotypic and virulence characteristics of cluster 3 isolates within the duck TMUV lineage. In this study, the etiological agent causing egg drop in a laying chicken farm in southern China was investigated and a TMUV was isolated from pooled tissue samples. Genome sequencing and phylogenetic analysis grouped the isolate into TMUV cluster 3 with closest relation to the mosquito‐origin TMUV YN12193. Cross‐neutralization testing using convalescent sera revealed significant antigenic variation between the isolate and a representative strain of cluster 2.2. The experimental infection of SPF hens confirmed the ability of the isolate to replicate in multiple tissues and led to ovary damage. Additionally, high seroconversion rates (95.83%–100%) were detected in the three flocks following retrospective investigation. Our study demonstrates the occurrence of cluster 3 TMUV infection in laying chickens and that the virus exhibits significant antigenic variation compared with cluster 2 TMUV.